Dinamika Sosial Budaya dalam Pengembangan Pariwisata di Desa Timbang Jaya Kabupaten Langkat - Khairi, Nurhafizhah (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2023)
Timbang Jaya Village is a tourist village established by the Regent of Langkat in 2021. The development of tourism in Timbang Jaya village is rapidly building various facilities and successfully entering the top 300 ADWI. However, the development of tourism has also experienced various significant socio-cultural dynamics within the Timbang Jaya community. This research uses a qualitative research approach that uses a community-based research model as a community effort to provide support, strength, resources, and participation in the research process to create informative research products. There are two formulations of the problem studied by the researcher. (1) What are the factors driving socio-cultural change in Timbang Jaya Village? (2) How is the socio-cultural change in tourism development in Timbang Jaya Village? Data sources in this study are primary and secondary data sources with observational data collection techniques, interviews and documentation, data analysis using data collection stages, data condensation, data presentation and conclusions. The results of this study show that tourism development in Timbang Jaya Village experiences socio-cultural dynamics. Many significant changes are seen in this case language changes, innovations, living order. The entry of new cultures results from the interaction between tourists and local communities. Keywords: tourism, Social dynamics, Social change